THREE-DIMENSIONAL MODELING OF SCOUR AND FLOW AROUND PILLARS USING FLOW 3D - Rasyid, Ilmiadin
The piers of the bridge cause the flow of the river to change, so that the hydraulic conditions of the river change too. One of the hydraulic changes is the increased shear stress at the bottom of the channel which has the potential to cause scour. Sediment transport will increase with increasing sediment shear stress, scour occurs when changes in flow conditions cause an increase in bed shear stress (Laursen, 1952 in Daties, 2012). This can be seen from the sediment transport equations of Meyer Peter Muller (1948), Van Nielsen (1992), Yang (2003) and Van Rijn (1984), when the flow shear stress is above the critical shear stress it will cause sediment transport. This study uses the RNG turbulence equation, the Meyer Peter Muller sediment transport equation and FLOW 3D software. The results of this study were obtained for one round pier, the bedload calibration parameter was 8 and the channel roughness calibration parameter was 2.5. The calculation of scour height, scour angle and flow have a fairly good similarity. Then these calibration parameters are used to simulate flow and scour on two rounded piers, two rounded corner piers and two triangular corner piers. The simulation results show that the shear stress is low around the piers and the maximum flow shear stress (0.315 N/ m2) is located far from the piers when compared to the simulations of other pier shapes. So it is obtained that the simulation on round piers is the best form in hydraulic calculations.